ANFIS based Most-Extreme Power Point Control Method for Isolated Solar PV System - D.Sabaripandiyan, H.Habeebullah Sait, G.Aarthi (International Journal of Advanced Science and Technology, 2020)
This paper proposes an Artificial Intelligent or hybrid control method for the Peak power point tracking of a photovoltaic (PV) system under inconsistent temperature and irradiation conditions. This method uses an ANFIS method that combines both ANN and Fuzzy Logic based controller applied to a DC-DC CUK converter device.  The maximum or Peak power controller receives solar radiation as one input and temperature as another input and provides the necessary duty ratio that will offer peak power as an output.  An isolated PV system with ANFIS based MPPT control is simulated and the result shows that the system with MPPT using ANFIS increases the efficiency of power extraction from the PV system.